Development of a training module on skills-based health education on sexuality for health professionals in private schools in the National Capital Region - Daniega, Desiree R.
Background of the study: Health education is one of the competencies which community and preventive medicine gives a lot of importance to. It can bring about significant changes in the knowledge, skills and attitudes towards health problems and issues, more so when an appropriate interventional is utilized in transmitting key health concepts and practices. The health professionals in schools, doctors nurses, have the advantage of doing so especially when they are properly equipped with the knowledge, skills and attitude needed to be effective health educators. Addressing the gap seen in the education and training of the health professionals in the school health in sexuality education is important in order to tackle the rising global concern on sexually transmitted diseases/HIV among the youth. Objectives: This paper examined the level of preparedness of health professionals in the health services of private schools on sexuality education prior to the development of skills based training modules on sexuality education. Methods: The research and development (R&D) research design was used in the study. A validated survey questionnaire was used in order to know whether the health professionals working in schools were prepared to do sexuality education effectively. A 57-item questionnaire of a five point-Likert scale was employed, with questions on knowledge, skills and attitude on human sexuality education. Development of the training module depended on the results of the needs assessment study and reviews of existing sexuality education modules. Likewise, a pilot test of the developed training module was done thereafter and results were analyzed using paired t-test. The participants were all active members of the Private Schools Health Officers Association in the National Capital Region practicing nursing and medical professions. Results: Data indicated that the level of preparation of health professionals in schools in the following areas needs reinforcement: (a) Knowledge, Current epidemiology of STDs/HIV, principles of diagnosis, investigation and management of STDs/HIV and one teaching strategy, role playing. (b) Skills, taking relevant sexual history and performing genital examinations (c) Attitude, managing lesbian/bisexual patients and relationship issues such as cohabitation before marriage and equating sexual relationships with maturity. In the development of the training program, several factors were considered, namely: (1) for content, focus on a comprehensive approach in teaching human sexuality (2) still on the content, focus on consequences in engaging into sexual relationships (3) determination of teaching strategies based on Knowles' adult learning theory which included, small group discussions, role-play, video/film showing, interactive lectures and case discussions and (4) Sequencing and scheduling of concepts based on the content focus and availability of the health professionals. Results after a training on skills based health education on sexuality of the health professionals demonstrated significant changes in the knowledge on the current epidemiology of HIV and STDs and principles of diagnosis, investigation and management of common STDs; skills in taking relative and sensitive sexual history and competence in performing genital examinations and, in attitude towards genital examination and managing lesbian/bisexual patients. The observed factors which hindered the effectiveness of the training program included: unfavorable setting specifically the schedule given by school administrators for training, lack of attention and focus due to work calls, and pre-formed opinions and ideas as expressed through nonverbal gestures. And on the other hand, factors which facilitated were high level of interest among the health professionals to participate and presence of initiative from the younger participants to share knowledge and views about the different concepts tackled. Recommendations: A larger number of participants should be surveyed and equal number of MDs and nurses should be invited for training, and to separate the two professions since they possess different competencies and educational trainings. Furthermore, a follow-up training after 3-4 months is encouraged. In developing and designing a training module, readiness of the health professionals and school administration to conduct the training, their schedule and work responsibilities should be taken into consideration. The development of a self-instructional material for the health professionals with a monthly short team discussion is also recommended given their busy schedule. And lastly for school administrators to study how they can make health professionals be more active in trainings and involvement in the implementation of school based sexuality education programs.